RUBBERISED COIR INDUSTRY - AN INTRODUCTION - P. Chandy Mathew (International Coconut Community, 1988)
The coconut palm is one of the versatile products of nature. Almost all parts of the tree are put to use by man. The uses of coconut kernel, shell, husk, trunk, leaves, sap etc., are well known and are therefore not described here. In this paper only one aspect of utilisation of coconut namely coconut fibre or coir for production of rubberised fibre is discussed in some detail. In major coconut producing areas more attention is given to utilisation of coconut kernel as this represents the most valuable portion of the coconut tree. It is therefore quite natural that most people concemed with coconut production and processing are less familiar with the by‑products of coconut. One such by‑product is rubberised coir which is a relatively capital intensive industry. In terms of